2009
DOI: 10.1124/dmd.109.028910
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Biotransformation of Pyrazinone-Containing Corticotropin-Releasing Factor Receptor-1 Antagonists: Minimizing the Reactive Metabolite Formation

Abstract: (S)-5-Chloro-1-(1-cyclopropylethyl)-3-(2,6-dichloro-4-(trifluoromethyl)-phenylamino)pyrazin-2(1H)-one (BMS-665053), a pyrazinone-containing compound, is a potent and selective antagonist of corticotropin-releasing factor receptor-1 (CRF-R1) that showed efficacy in the defensive withdrawal model for anxiety in rats, suggesting its use as a potential treatment for anxiety and depression. In vitro metabolism studies of BMS-665053 in rat and human liver microsomes revealed cytochrome P450-mediated oxidation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…The attractive in vivo pharmacology and disposition properties of the pyrazinone derivative 9 (Scheme 11.9) were offset by the finding that 9 was bioactivated by P450 to form reactive metabolites. In fact, a major component of the elimination mechanism of 9 in rats (∼40% of drug-related material recovered in rat bile) is composed of conjugation with GSH, which is consistent with reactive metabolite formation in vivo [76]. Two distinct bioactivation pathways were deciphered (Scheme 11.9): (i) oxidative metabolism on the chloropyrazinone ring to yield an electrophilic epoxide and (ii) O-dealkylation of the difluoromethylphenoxy moiety to yield a phenol metabolite 10, two electrons in which generated the reactive quinone-imine species in a manner similar to that discerned with the 2,6-dichloro-4-hydroxyaniline analogs and NSAIDs diclofenac and lumiracoxib [77,78].…”
Section: Examples Of Medicinal Chemistry Tactics To Eliminate/minimizsupporting
confidence: 54%
“…The attractive in vivo pharmacology and disposition properties of the pyrazinone derivative 9 (Scheme 11.9) were offset by the finding that 9 was bioactivated by P450 to form reactive metabolites. In fact, a major component of the elimination mechanism of 9 in rats (∼40% of drug-related material recovered in rat bile) is composed of conjugation with GSH, which is consistent with reactive metabolite formation in vivo [76]. Two distinct bioactivation pathways were deciphered (Scheme 11.9): (i) oxidative metabolism on the chloropyrazinone ring to yield an electrophilic epoxide and (ii) O-dealkylation of the difluoromethylphenoxy moiety to yield a phenol metabolite 10, two electrons in which generated the reactive quinone-imine species in a manner similar to that discerned with the 2,6-dichloro-4-hydroxyaniline analogs and NSAIDs diclofenac and lumiracoxib [77,78].…”
Section: Examples Of Medicinal Chemistry Tactics To Eliminate/minimizsupporting
confidence: 54%
“…79 Additional metabolite ID studies on 142 revealed that the pyrazin-2(1H)-one was susceptible to oxidation and GSH conjugation. 78 The suggested intermediate that led to pyrazin-2(1H)-one metabolism was the chloroepoxide 146, which after hydrolysis or reaction with GSH led to the observed oxidized metabolites 149 and 150 and GSH adducts 147 and 148. Metabolism was also observed on the arylamine portion of 142 but to a lesser extent.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…Instead, the most commonly utilized approach is to capture the reactive intermediate with a trapping agent, leading to formation of stable adducts of reactive metabolites that can be detected and characterized using LC-MS/MS techniques [4][5][6]. These methods have been extensively applied to efforts in the minimization of bioactivation for lead compounds at the drug discovery stage [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%